EMPLOYEE PERFORMANCE BASED ON WORK MOTIVATION, EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL COMMITMENT - Andika, Adi; Sudarijati, Sudarijati; Silaningsih, Endang (Universitas Nusa Cendana, 2025)
This study aims to assess employee perceptions and examine the direct effects of work motivation and employee engagement on organizational commitment, as well as the direct effects of work motivation, employee engagement, and organizational commitment on employee performance. It also investigates the indirect role of organizational commitment in mediating the impact of work motivation and employee engagement on employee performance. Using path analysis and a sample of 132 respondents, the study found that work motivation and employee engagement significantly influence organizational commitment. Additionally, all three variables—work motivation, employee engagement, and organizational commitment—directly affect employee performance. Organizational commitment also serves as a mediating factor between both work motivation and employee engagement on employee performance. Keywords: Work Motivation; Employee Engagement; Organizational Commitment; Employee Performance